Configurational comparative methods : qualitative comparative analysis (QCA) and related techniques - Rihoux, Benoît 1965- HerausgeberIn; Ragin, Charles C. HerausgeberIn (Applied social research methods series, 2009)
Provides details on a specific approach to research. The book is relevant to a broad range of disciplines, can be used in teaching and by practitioners, and is focused on an integrated approach to qualitative and quantitative research